Empowering Dyslexic children’s literacy through mobile applications and multisensory: addressing the challenges faced by special needs teachers / Noratikah Abdullah, Mariam Mohamad and Mageswaran Sanmugam - Abdullah, Noratikah; Mohamad, Mariam; Sanmugam, Mageswaran (Universiti Teknologi MARA, Kedah, 2023)
Dyslexia is a common learning disorder that affects a child's ability to read, write, and spell. Special needs teachers face significant challenges in addressing the unique learning needs of dyslexic students. This paper proposes the use of mobile applications and multisensory approaches to empower dyslexic children's literacy skills and address the challenges faced by special needs teachers. The paper draws on existing literature and including field test on dyslexia and mobile learning to support the argument that mobile applications offer a cost-effective and accessible means of supporting dyslexic children's learning. The paper also explores the role of multisensory approaches in enhancing literacy skills for dyslexic children. The proposed approach has the potential to address some of the challenges faced by special needs teachers in teaching dyslexic children. For example, mobile applications can provide dyslexic students with individualized learning experiences, while multisensory approaches can help dyslexic students overcome the challenges of traditional teaching methods. Overall, the paper argues that the use of mobile applications and multisensory approaches can empower dyslexic children's literacy skills and address the challenges faced by special needs teachers. By leveraging technology and innovative teaching methods, we can create a more inclusive learning environment for dyslexic children.